The Impact of Pop Music on Teenagers’ Music Aesthetics under Short Video: Taking Tiktok "Subject 3" as an Example - Su, Yan (International Journal of Social Sciences and Public Administration, 2024)
Popular music, also known as "popular music", has developed rapidly in China in recent years and is deeply loved by the public. With the popularity of smart phones and the development of the Internet, short video software has gradually emerged. The platform represented by Tiktok has brought a new path to the development of popular music. A batch of popular music that is popular with short videos has set off a boom in all age groups. Teenagers account for the largest proportion of Internet users. This paper briefly discusses the impact of short videos on teenagers and popular music, analyzes the aesthetic characteristics of teenagers’ music, and takes Tiktok "Subject 3" as an example, the characteristics of popular music under the background of short videos and its positive aesthetic impact on teenagers, and provides reference and suggestions for cultivating teenagers’ aesthetic appreciation of music.